Pole-arizing extremes : negotiating deviance and achieving empowerment in recreational pole dancing - Yeo, Nicholas (2019)
This paper aims to explore the reasons behind why recreational pole dancers are labelled as deviants, and the methods they engage in to negotiate this label. Information was gathered from both surveys and informal semi-structured qualitative interviews. For the interviews, 10 individuals revealed in-depth details regarding their pole dance journey. All of our interviewees highlighted to us how they felt stigmatized at some point and were casted as deviants. However, rather than simply withdrawing their participation, they negotiated these deviant labels through various strategies under Sykes and Matza’s Techniques of Neutralization (1957). They also emphasised how pole dancing has allowed them to experience feelings of empowerment on both personal and societal levels. However, despite their attempts, societal limitations such as “double entanglement” (McRobbie, 2009) and a highly communitarian Singaporean culture still prevents them from achieving true empowerment and expressing themselves without restraint in the eyes of the Singaporean public.